Discovery of novel small molecule modulators of Clavibacter michiganensis subsp. michiganensis - Xu, Xiulan; Kumar, Anand; Deblais, Loïc; Pina-Mimbela, Ruby; Nislow, Corey; Fuchs, James R.; Miller, Sally A.; Rajashekara, Gireesh (Frontiers in Microbiology, 2015)
Clavibacter michiganensis subsp. michiganensis (Cmm) is a Gram-positive seed-transmitted bacterial phytopathogen responsible for substantial economic losses by adversely affecting tomato production worldwide. A high-throughput, cell-based screen was adapted to identify novel small molecule growth inhibitors to serve as leads for future bactericide development. A library of 4,182 compounds known to be bioactive against Saccharomyces cerevisiae was selected for primary screening against Cmm wild-type strain C290 for whole-cell growth inhibition. Four hundred sixty-eight molecules (11.2% hit rate) were identified as bacteriocidal or bacteriostatic against Cmm at 200 M. Seventy-seven candidates were selected based on Golden Triangle analyses for secondary screening. Secondary screens showed that several of these candidates were strain-selective. Several compounds were inhibitory to multiple Cmm strains as well as Bacillus subtilis, but not Pseudomonas fluorescens, Mitsuaria sp., Lysobacter enzymogenes, Lactobacillus rhamnosus, Bifidobacter animalis, or Escherichia coli. Most of the compounds were not phytotoxic and did not show overt host toxicity. Using a novel 96-well bioluminescent Cmm seedling infection assay, we assessed effects of selected compounds on pathogen infection. The 12 most potent novel molecules were identified by compiling the scores from all secondary screens combined with the reduction of pathogen infection in planta. When tested for ability to develop resistance to the top-12 compounds, no resistant Cmm were recovered, suggesting that the discovered compounds are unlikely to induce resistance. In conclusion, here we report top-12 compounds that provide chemical scaffolds for future Cmm-specific bactericide development.